Family Income in Relation to Budgeting of Accounting Students in A University - Jumawan-Powao, April R.; Tubat, Krizia T.; Cellero, Rio Cyrel L; Alibangbang, Arthur Dave C.; Capilitan, Ma. Khym T. (Future Science / FSH-PH Publications, 2024)
The current economic conditions and financial issues are becoming increasingly important as students face more complex challenges in managing their money. Nowadays, students need to be more aware of these challenges, which may pose a threat to their future success. Thus, the conduct of this study would be beneficial in order to bring light to the restraining results found from other literature and contribute to the body of knowledge aligned with this study. This study aims to understand the correlation between the family income and its effects towards the student budgeting, and whether sex, as a moderating variable, is related to the independent and dependent variables. The study employed descriptive-correlation design and random sampling method, particularly Slovin’s formula, to identify the total sample from the population of accounting students in the University. The statistical treatments used were descriptive statistics and inferential statistics to test the relationships of the variables particularly the relationship of family income towards budgeting and allowance and the relationship of allowance towards budgeting. Meanwhile, Mann Whitney U-test was used to test the differences of the participants when grouped in terms of sex. The results of the study depict that there is no significant difference in the budgeting of participants when they are grouped in terms of sex and there is an indirect relationship between family income and budgeting. Based on the results, researchers may recommend conducting a community extension initiative aimed at developing financial literacy among students.